The Relationship between the Implementation of Patient Safety and Patient Satisfaction in the Adult in Patient Room - Dwi Rohyani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patients who are dissatisfied with nursing services in Indonesia or in several other developing countries are currently a very urgent problem. The quality of service can have an influence on the level of patient satisfaction, when the quality of the service provided is poor, then the level of patient satisfaction will certainly also be bad. The quality of health services that can increase the level of patient satisfaction can be sourced from relatively specific factors, one of which is implementing patient safety targets. This research is to determine the relationship between patient safety implementation and patient satisfaction in the adult inpatient room at Hospital X Jakarta. This research uses a correlative descriptive design method with a cross sectional approach. The sampling technique uses non-probability sampling with purposive sampling technique. The sample obtained was 74 respondents using the Slovin formula. The statistical test used is chi-square. The research instrument used a questionnaire. This research shows that there is a relationship between the implementation of patient safety and the satisfaction of adult inpatients at Hospital X Jakarta. This was proven by the chi-square test, the p-value was: 0.002 (p<0.05). That the implementation of patient safety can influence patient satisfaction.